Normal sensory conduction in the nerves of the leg in man. Issue 4 (August 1971) - Behse, Friedrich; Buchthal, Fritz
Abstract : For comparison with findings in neuropathy, sensory conduction was studied along distal and proximal segments of the superficial peroneal, sural, and posterior tibial nerves in 71 healthy subjects 15 to 72 years of age and normal values were established (Table 2). In the distal segments of the nerves of the leg the amplitudes of the sensory potentials were one tenth those in the nerves of the upper extremity; the potentials were split up into several components, and electronic averaging was used routinely to analyse the shape of the potentials. The maximum sensory conduction velocity was 56·5 m/sec, SD 3·4 m/sec, in proximal; and 46·1 m/sec, SD 3·7 m/sec, in distal segments of the nerves (subjects 15 to 30 years, 34 to 36°C). Slowing of conduction with increasing age was the same proximally and distally (subjects 40 to 65 years: proximally 53·1 m/sec, SD 4·6 m/sec; distally 42·5 m/sec, SD 5·5 m/sec, 34 to 36°C). The velocity in the slowest components of the sensory potentials averaged 20 m/sec. The sensory velocity was 3 to 6 m/sec faster than the motor. The error arising from measuring the conduction distance on the surface across the capitulum fibulae was evaluated.